Inkjet 3D Printed Micropot with Integrated Cantilever-Like Force Sensor for Growing Plant Biological Potential Measurement - Krzysztof Adamski; Bartosz Kawa; Rafał Walczak (Proceedings, 2019)
In this paper we present a results of fabrication of 3D printed micropot with integrated cantilever-like force sensor. Different thickness cantilevers was used. Presented micropot was use for characterization of grow Lepidium sativium.